2020
DOI: 10.1080/2162402x.2020.1777624
|View full text |Cite
|
Sign up to set email alerts
|

Trial watch: STING agonists in cancer therapy

Abstract: Stimulator of interferon response cGAMP interactor 1 (STING1, best known as STING) is an endoplasmic reticulum-sessile protein that serves as a signaling hub, receiving input from several pattern recognition receptors, most of which sense ectopic DNA species in the cytosol. In particular, STING ensures the production of type I interferon (IFN) in response to invading DNA viruses, bacterial pathogens, as well as DNA leaking from mitochondria or the nucleus (e.g., in cells exposed to chemotherapy or radiotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
162
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(167 citation statements)
references
References 191 publications
(245 reference statements)
2
162
0
3
Order By: Relevance
“…Based on these findings, we hypothesized that pharmacological activation of the cGAS/STING pathway would further augment PARP inhibitor-induced inflammatory signaling and consequent anti-tumor immune responses. We utilized the PARP inhibitor olaparib and the STING agonist ADU-S100, which has been shown to lead to potent anti-tumor immunity in multiple tumor models (9,10) and is currently in clinical trials (8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, we hypothesized that pharmacological activation of the cGAS/STING pathway would further augment PARP inhibitor-induced inflammatory signaling and consequent anti-tumor immune responses. We utilized the PARP inhibitor olaparib and the STING agonist ADU-S100, which has been shown to lead to potent anti-tumor immunity in multiple tumor models (9,10) and is currently in clinical trials (8).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we have investigated an alternative approach to improving efficacy in BRCA-associated breast cancer by combining PARP inhibition with STING agonism. STING agonists have entered clinical trials and combinations with chemotherapy or immune checkpoint blockade have demonstrated preliminary safety and efficacy (8). In this study, we sought to develop the preclinical rationale for combining STING agonists with PARP inhibition.…”
mentioning
confidence: 99%
“…5 Similar, in addition to the chronic activation of the STING1 pathway that mediates genomic instability-induced tumorigenesis and metastasis, 6 the robust activation of the STING1 pathway by reagents (e.g., MSA-2, DMXAA, ADU-S100, and zalcitabine) or radiation therapy is an approach to enhance antitumor immunity or direct killing cancer cells in mouse models or clinical trials. [7][8][9] Acute activation of STING1-mediated T cell apoptosis may weaken anti-tumor immunity, 10 further arguing the dual role of STING1 in tumor therapy. Thus, it will be important to identify key DAMP mediators and to decipher the molecular mechanisms that explain reprogramming from immune activation to tolerance during tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The nanoparticle-based delivery of the STING activator has also increased the antitumor immune response (increased M2 to M1 macrophage polarization, IFN-Îł producing T cells, tumor cell apoptosis, and CD4 + and CD8 + T cell infiltration in the tumor microenvironment) in the PD-L1-insensitive triple-negative breast cancer ( 160 ). Different STING agonists are under phase I and II clinical trials ( 161 ). The results will determine their progression to the large phase III clinical trials.…”
Section: Cgas-sting-based Host Cell Dna Recognitionmentioning
confidence: 99%